Newly Diagnosed Primary Immune Thrombocytopenia in Children: Which Guideline to Adhere? - Mahendra, Cipta (SCRIPTA SCORE Scientific Medical Journal, 2021)
Background: Immune thrombocytopenia purpura (ITP) is an autoimmune disorder of bleeding which is defined as having thrombocytopenia (platelet count below 100.000/ÂµL). Most ITP cases in children are acute and recent various guidelines have established a wait-and-see protocol as management for children with ITP since it is assumed to be temporary and will most likely to resolve spontaneously. Objectives: For this case report, a case of primary ITP in a child will be discussed. In the following discussion section, several ITP consensus guidelines will be discerned and compared to see which is the more appropriate guideline to adhere in managing a newly diagnosed ITP case in children. The case report is used as a â€˜triggerâ€™ to dissect the core treatment suggestions described in the inspected consensus guidelines. Case Illustration: A 6-years-old female child presents to a hospital with a chief complaint of having red spots in her arms and legs since a day ago. The red spots she complained was the first time to be experienced. She had no prior fever, (bloody) diarrhea, nausea, and vomiting. Physical examination showed no remarkable abnormalities other than numerous petechiae in the upper and lower extremities. Discussion: The patient in this case was finally admitted and treated in the hospital as an inpatient with corticosteroid, antibiotics, and platelet concentrates despite the current guidelines that generally advocate against these treatments. This case report may give an insight regarding the factors needed to be considered before treating a child with newly diagnosed ITP. Conclusion: The Joint Working Group (JWG) consensus seems to be the most comprehensive guideline in treatment of newly diagnosed ITP in children, compared to the American Society of Hematology (ASH) and International Consensus Report guideline. Keywords: hematology, ITP, newly diagnosed, primary, thrombocytopenia Â  Latar Belakang: Immune trombositopenia purpura (ITP) merupakan sebuah penyakit perdarahan otoimun yang didefinisikan sebagai adanya trombositopenia (trombosit dibawah 100.000/ÂµL). Mayoritas kasus ITP pada anak bersifat akut dan konsensus terkini menyarankan protokol â€œwait and seeâ€ sebagai tatalaksana untuk anak dengan ITP karena dianggap hanya sementara dan cenderung akan membaik secara spontan. Tujuan: Untuk laporan kasus ini, sebuah kasus ITP primer pada anak akan dibahas. Pada bagian diskusi, beberapa panduan terkait ITP akan diulas dan diperbandingkan untuk melihat panduan mana yang paling sesuai untuk mengatasi kasus baru (newly diagnosed) ITP pada anak. Laporan kasus ini digunakan sebagai pengantar untuk membahas intisari tatalaksana ITP dalam konsensus-konsensus yang dipakai. Ilustrasi Kasus: Anak perempuan berusia 6 tahun datang ke rumah sakit dengan keluhan utama adanya bintik-bintik merah pada kedua lengan dan tungkainya sejak sehari lalu. Bintik-bintik merah tersebut baru pertama kali dialami. Dia tidak menderita demam, diare (berdarah), nausea, dan vomitus. Pada pemeriksaan fisik, hanya ditemukan petekie-petekie di kedua ekstremitas atas dan bawah. Pembahasan: Pasien dalam kasus ini dirawatinapkan dan diberi kortikosteroid, antibiotik, dan konsentrat trombosit sebagai tatalaksananya, meskipun panduan-panduan yang ada secara umum tidak menyarankan tatalaksana demikian. Laporan kasus ini diharapkan memberikan wawasan terkait faktor-faktor yang penting untuk dipertimbangkan sebelum merawat seorang anak dengan kasus baru ITP. Kesimpulan: Konsensus Joint Working Group (JWG) tampaknya menjadi panduan paling komprehensif dalam tatalaksana anak dengan kasus baru ITP, dibanding panduan American Society of Hematology (ASH) dan International Consensus Report. Kata Kunci: hematologi, ITP, newly diagnosed, primer, trombositopenia